Lean Inventory Management Systems and Performance of Supermarkets in Nairobi County, Kenya - Achuora, John; Arasa, Robert (International Academy of Business and Economics, 2020)
Lean inventory management systems (LIMS) is postulated to have the capability of enhancing performance of firms through minimization of overheads associated with inventory management in firms where inventory forms a significant portion of operational costs. Therefore in this study LIMS(s); just-in-time, cross-docking, drop shipping and back ordering were theorized to have an impact on the performance of supermarkets in Nairobi County, Kenya. The study used of a descriptive research design and surveyed 113 supermarkets randomly sampled from 158 supermarkets in Nairobi City County. A structured questionnaire was used as the primary data collection instrument. The questionnaire was administered through drop and pick later mode to the respective supply chain managers of the supermarkets. The instrument was piloted for validity, reliability and to identify potential gaps. Multiple regression model was applied to test the study hypothesized model and the statistical package for social science (version 21.0) facilitated the tests. The tests established a positive significant link between lean inventory management systems and performance of supermarkets. This implies that an increase in use of lean inventory management systems in the operations of supermarkets, increases their performance positively. The study further established that just in time system had the highest influence on supermarkets performance followed by back ordering, drop picking and cross-docking respectively. The study concludes that lean inventory management systems such as just-in-time, cross docking, drop shipping and back ordering improve supermarket performance. The study recommends that retail supermarket owners/managers should implement an inventory policy in support of lean inventory management practices, define stock keeping units to better understand and forecast demand. Secondly, supermarket owners should make profound cultural changes to re-enforce a lean transformation and develop a performance culture focusing continuous improvement where staff are always actively discussing and implementing improvements through either formal or informal. Finally supermarket owners/managers need to close the gap by hiring a few people with lean expertise and experience from outside the retail sector to seed the transformation and build new internal capabilities in lean inventory management practices in managing their inventory
Keywords: Backordering; Cross-Docking; Drop Shipping; Just-In-Time